Breakfast Pattern, Nutritional Status, and Nutritional Intake of School-Age Children (Studies in Fifth-Grade Students of Kartika Elementary School, Banyu Urip, Surabaya) - Lestari, Yanesti Nuravianda; Pitaloka, Retha; Oktavia, Lyna; Sari, RR. Dea Nanda Febri Lukita; Hasanah, Uswatun; Mardiana, Dinda Ayu; Fadila, Nur; Amin, Nur (Universitas Nahdlatul Ulama Surabaya, 2021)
Breakfast is necessary because it contributes 15-30% of the total daily energy needs to support the maintenance of physical endurance, energy balance and increase work productivity. This study aims to analyze the relationship of breakfast pattern to nutritional status and dietary intake in 5th-grade students of Kartika Elementary School, Banyu Urip, Surabaya. Descriptive correlational research with a cross-sectional design using the subjects of fifth-grade students of Kartika Elementary School, Banyu Urip, Surabaya using total sampling (n=57 students aged 10-13 years). Statistical test analysis of data using Spearman's Correlation Test. The results showed that most of the subjects were male (56.11%). The subjects' Body Mass Index is between 13.71 – 33.47 kg/m2, and the nutritional status (BMI for age) of research subjects ranged from -2.46 SD to 3.73 SD. The correlation analysis results showed that the breakfast pattern is not significantly related to nutritional status (p=0.913). Breakfast pattern are also not significantly related to energy and nutrient adequacy levels (p=0.655; 0.347; 0.999; 0.760; and 0.235). It can be concluded that breakfast pattern is not related to nutritional status and daily dietary intake.